1988
DOI: 10.1180/minmag.1988.052.368.11
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence Colours of α-Quartz

Abstract: A new cathodoluminescence-microscope has been developed with a considerably improved detection limit. Time-dependent luminescence intensity changes observed during electron bombardment enabled the recognition of short-lived, long-lived, and brown luminescence colour types in ~-quartz.Short-rived bottle-green or blue luminescence colours with zones of non-luminescing bands are very common in authigenic quartz overgrowths, fracture fillings or idiomorphic vein crystals. Dark brown, short-lived yellow or pink col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 12 publications
2
79
0
Order By: Relevance
“…Additional images were taken after 1 to 3 min of electron irradiation to reveal any changes in the CL. Through this technique, it was possible to document the transient blue CL which is a characteristic feature of hydrothermal quartz [Ramseyer et al, 1988;Ramseyer and Mullis, 1990;Perny et al, 1992;Götze et al, 2001]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional images were taken after 1 to 3 min of electron irradiation to reveal any changes in the CL. Through this technique, it was possible to document the transient blue CL which is a characteristic feature of hydrothermal quartz [Ramseyer et al, 1988;Ramseyer and Mullis, 1990;Perny et al, 1992;Götze et al, 2001]. …”
Section: Methodsmentioning
confidence: 99%
“…This type of transient CL response is characteristic of hydrothermal quartz [Ramseyer et al, 1988;Götze, 1996] and is attributed to (1) and Mullis [1990], Perny et al [1992]), and (2) photon emission associated with the recombination of electrons in the nonbridging oxygen band-gap state [Siegel and Marrone, 1981]. Silanol groups may be the precursor of this second type of emission center in hydrothermal quartz, which is characterized by orange to red CL (620-650 nm).…”
Section: Quartz-epidote Veinsmentioning
confidence: 99%
“…If quartz with brown or red CL response is typical of quartz from metamorphic rocks (Zinkernagel 1978;Ramseyer et al 1988;Boggs et al 2002), the reddish brown luminescent fluid migration trails observed suggest that some "quartz eyes" underwent retrograde metamorphic fluid reaction. But the reddish-brown and reddish CL colours can also be explained by lattice defects induced by twinning, mechanical deformation, or rapid growth (Ramseyer et al 1988).…”
Section: Origin Of Quartz Eyesmentioning
confidence: 99%
“…The defects causing different CL emissions often reflect the specific physico-chemical conditions of crystal growth and therefore can be used to investigate genetic conditions. Then, according to classification schemes relating the quartz CL colour to the genetic environment (Zinkernagel 1978;Ramseyer et al 1988), the mostly bright bluish and rarely red colours observed suggest "quartz eyes" have a phenocrystic origin (i.e., similar to quartz crystals in volcanic rocks). Likewise the stable luminescence behaviour exhibited by all quartz crystals is indicative of crystallization at higher temperatures, i.e.…”
Section: Origin Of Quartz Eyesmentioning
confidence: 99%
“…Mineral non-stoichiometry, poor crystallographic ordering, lattice defects and the incorporation of trace elements into a crystal structure can generate cathodoluminescence ("CL") of varying wavelengths and intensity, which is useful for interpreting a variety of geological phenomena (Marshall, 1988;Ramseyer et al, 1988;Trukhin, 1994;Götze et al, 2001), including the nature of quartz depositional processes (water-rock interaction) in active geothermal settings (Bignall et al, 2004). CL is caused by the emission of photons in response to electron bombardment, and can be observed using a scanning electron microscope (SEM) equipped with a CL detector.…”
Section: Introductionmentioning
confidence: 99%